The Concept of Istita'˜ah Al-Ba’ah in Marriage - Taufiq Hidayat; Raihanah Azahari (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2020)
Islam has to the law of sharia a marriage between men and women to build a family that is sakinah, mawaddah, and rahmah. To achieve the goal of marriage, Islam has set a requirement for married couples to have several abilities to marry, termed as istita'ah al-ba'ah. Practically, there are still many people in marriages who understanding the concept of istita’ah al-ba’ah partially and even not applied it at all. This study aims to examine the concept of istita’ah al-ba’ah as a requirement in marriage and to explain its types and criteria according to sharia perspective through library research on Fiqh Principle and content analysis of Fiqh books. This study profoundly analyses the collective data. This study has successfully found the types and criteria of marriage recommended in marriage, firstly, non-material abilities including an ability to have sex, physical health from dangerous diseases, and age. The second is a material ability, including an ability to meet the cost of marriage consisting of paying dowry and living. This study contributes to the context of strengthening the ability standards for couples wishing to get married. Therefore, fulfilling the requirements of marrying is expected to minimize marriage problems, including minimizing the divorce rate.